PENGAWASAN PERTAMBANGAN BATUBARA OLEH DINAS PERINDAGKOPNAKER KOTA SAWAHLUNTO PROVINSI SUMATERA BARAT (STUDI KASUS WILAYAH IZIN USAHA PERTAMBANGAN) - Elfitri Adlin; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
In Sawahlunto, mining coal still has problem about license of mine operation each license of mine operation holder. Sawahlunto government has been establishing Perindagkopnaker Department to control mining coal at license of mine operation zone. This research’s problem is how is the controlling mining coal at license of mine coal operation zone in Sawahlunto and what the influence factors are.The controlling is not to see the weakness or frailty but to prevent, decrease or abolish all deviations happens in an organization. The researcher uses controlling theory by Manullang. Based on this theory there are many controlling processes should be use in order do controlling, the researcher uses controlling which close with indicator of establish measurement, doing evaluation and improvement action. This research uses descriptive explanations that is the analysis to give description of cause and effect connection based on reality found on the field, and then descriptive data of interview and observation presentation will be concluded.The research result point out the controlling of mining coal at license of mine coal operations zone in Sawahlunto West Sumatera done by Perindagkopnaker Department Sawahlunto has not success yet. There are some flows like in doing evaluationand improvement is not going well yet. It caused of controlling factors such as man resources, cost, and public participant level.Key Words : Controlling, Mining Coal, Perindagkopnaker Department